IMPLEMENTASI PERATURAN DAERAH NO. 3 TAHUN 2010 TENTANG PENGELOLAAN DAN PENYELENGGARAAN PERPARKIRAN DI KOTA BUKITTINGGI (STUDI KASUS PADA PENENTUAN LOKASI, PENGADAAN DAN PEMBANGUNAN GEDUNG PARKIR DAN PELATARAN PARKIR) - Saputri, Fina Rahmi; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bukittinggi city is one of trade centers and tourist resorts in West Sumaterathat attract many people to visit this place. Not only local people but also otherpeople from other cities are very interested in Bukittinggi. As the result, the parkingproblem has been becoming much more seriously important in this city. Parkingspaces capacity cannot meet the needs of parking demand for visitors. The problemsof this research are how the implementation of the regional regulation no 3 of 2010about parking management and supply in Bukittinggi and the factors that influencethe implementation.This research used policy implementation theory by Van Mater and VanHorn. This theory consists of six variables that include standard and objective, policyresources, activities between organizations and executive activities, implementingagencies characteristics, economic, social and politic condition and the dispositionsof implementers. The method of this research was qualitative using snowballsampling technique in selecting the key informants. The key informants in thisresearch were the Department of Transportation, Communication and InformationBukittinggi, Department of Public Work Bukittinggi, parking attendants and society.Based on the research, it was found that the implementation of RegionalRegulation no 3 of 2010 about Parking Management and Supply in Bukittinggi didnot run well. The Department of Public Work constructed a parking building but theparking was not managed well. This condition occurred because the regulation wasnot properly disseminated and lack of parking attendants to manage the parking inBukittinggi. Therefore, many people did not aware of the parking building.Key words: Implementation, Regional Regulation, Management, Supply, Parking,Parking Building.